Humanidades digitales: la censura y los laudatorios en las preliminares del Siglo de Oro español; Madrid y Guzmán de Alfarache (2016)
This article represents the final result of a research project. The purpose was Understanding the stories of some voices of actors schoolchildren the collective memory of the César Conto Departamental Educational Institution about the slaughter from Bojayá, Chocó, as a relevant element to the recovery of collective memory. For this purpose, it was used as a methodology, because it made easy the understanding of the voices of the chosen actors. The research revealed: One) the sense and the meaning of the slaughter for the people; two) the affectations to the educative process; three) the sociocultural transformations and the impact lived for the César Conto Departamental school, Bajaya town and its surroundings; four) theViolations of Human Rights and International Humanitarian Law; and five) the responsibility of the Colombian Statebusinessmen and landowners in the armed conflict that has been waged in this part of the country